2008
DOI: 10.1097/mph.0b013e31818a953e
|View full text |Cite
|
Sign up to set email alerts
|

Transient Myeloproliferative Disorder in Neonates With and Without Down Syndrome

Abstract: Transient myeloproliferative disorder (TMD) in newborns with Down syndrome (DS) has been well described. We report 4 newborns, 2 with DS and 2 without DS, who developed TMD. One newborn with DS developed multiorgan failure and died despite treatment with low-dose cytarabine. In 3 newborns, the TMD resolved spontaneously. Two of these patients, 1 with and 1 without DS developed leukemia on subsequent follow-up and were treated successfully. We reviewed the clinical and laboratory data on 14 non-DS infants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Trisomy 21, however, may only be present in a proportion of tissues including the hematopoietic one in infants, with TL lacking the typical features of DS (trisomy 21 mosaicism) (Zipursky 2003 ;Gamis et al 2011 ). In fact, trisomy 21 may be confi ned only to a proportion of hematopoietic cells, including normal cells and the TL blast population, or exclusively to the population of TL blasts (Apollonsky et al 2008 ;Ono et al 2015 ;Tsai et al 2011 ). Trisomy may involve the entire chromosome 21 or a specifi c part (segmental trisomy 21) (Korbel et al 2009 ;Korenberg et al 1994 ).…”
Section: Trisomy 21 (Constitutional Mosaicism Somatic)mentioning
confidence: 94%
“…Trisomy 21, however, may only be present in a proportion of tissues including the hematopoietic one in infants, with TL lacking the typical features of DS (trisomy 21 mosaicism) (Zipursky 2003 ;Gamis et al 2011 ). In fact, trisomy 21 may be confi ned only to a proportion of hematopoietic cells, including normal cells and the TL blast population, or exclusively to the population of TL blasts (Apollonsky et al 2008 ;Ono et al 2015 ;Tsai et al 2011 ). Trisomy may involve the entire chromosome 21 or a specifi c part (segmental trisomy 21) (Korbel et al 2009 ;Korenberg et al 1994 ).…”
Section: Trisomy 21 (Constitutional Mosaicism Somatic)mentioning
confidence: 94%
“…7 A retrospective review reported that five of 16 patients with TMD without DS developed subsequent leukemia, three developed AMKL, and two developed non-AMKL acute myeloid leukemia, but patients were not checked for the presence of GATA1 mutations. 4 Our patient developed AMKL subsequent to TMD. She had high WBC with TMD, spontaneous remission, and reappearance of megakaryoblasts with lower WBC.…”
Section: Discussionmentioning
confidence: 99%
“…TMD also occurs in children without DS who have either mosaicism for trisomy 21 or normal karyotype. 4 The frequency and pathogenesis of TMD and subsequent AMKL in these children is not well known because TMD may go undetected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient abnormal myelopoiesis and subsequent AMKL with acquired trisomy 21 has also been observed in phenotypically normal and/or cytogenetically normal infants albeit much less commonly [5][6][7]. In such cases, the status of GATA1 has been rarely characterized [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 93%